IMPLICATIONS OF THE BAWKU CHIEFTAINCY CONFLICT ON BASIC EDUCATION IN THE BAWKU TRADITIONAL AREA OF THE UPPER EAST REGION OF GHANA - Alhassan, E.; Abdul-Karim, I.; Degraft Arthur, D. (UDS International Journal of Development, 2017)
Ghana is locally and internationally described as an oasis of peace and stability in a continent circumvented by conflicts. This is because the country has not experienced any civil war or large-scale violence since independence in March 1957. Nevertheless, it is faced with pouches of relative violence, including ethnic conflicts, land/resource based conflicts, religious violence and chieftaincy disputes, having devastating implications on socio-economic development. This paper contributes to the debate on the implications of the Bawku chieftaincy conflict on basic education in the Bawku Traditional Area of the Upper East Region of Ghana. The Protracted Social Conflict Theory underpinning the Bawku chieftaincy conflict was examined. Data for the study were drawn from both primary and secondary sources, comprising books, articles, journals, newspapers, theses, interviews and focus group discussions. The study revealed that the conflict has had devastating effects on basic education in the area in terms of completion rates, gender equality, educational attainment rates and educational infrastructure. To minimise the adverse effects of the conflict on basic education in the area, the paper recommends campaign on the implications of the conflict on the socio-economic development of the area, particularly on basic education by the government, non-governmental organisations and opinion leaders. Keywords: Conflict, chieftaincy, education, development, Bawku, GhanaÂ